Autologous graft from portal vein for reconstruction of the middle hepatic vein after hepatectomy. Issue 1 (12th January 2021) - Fan, Sheung Tat
Abstract: Objective: To evaluate the efficacy of right or left portal vein retrieved from patient's own hepatectomy specimen as a graft for reconstruction of the middle hepatic vein. Methodology: Three patients had resection of cranial half of the middle hepatic vein with the adjacent tumor. The right or left portal vein was removed from the hepatectomy specimen and used as a graft for reconstruction of the middle hepatic vein. Results: After a follow up period of 2 months to 13 years, the vein graft remained patent. Tumor recurrence was not seen. Conclusion: Autologous graft from portal vein in hepatectomy specimen is an effective source for reconstruction of the middle hepatic vein after hepatectomy.